Pathological changes of suspected tetrachloro dibenzo-ï²-dioxins/tetrachloro dibenzofurans toxication in beef cattle - Sani, Yulvian; Indraningsih, . (Indonesian Animal Sciences Society, 2015)
The contamination of tetrachlorodibenzo-r-dioxins (TCDDs) and tetra chlorinated dibenzofurans (TCDFs) may affect human or animal health such as cancer, reproductive failure, dermaltoxicities and neurologic effects. The present study describes the effects of TCDD/TCDFs contamination in feed to various tissues of beef cattle to which TCDD/TCDFs were detected byGC MS/MS. The results revealed that POPs (DDT, heptachlor, aldrin, dieldrin and endrin) as a precursor for dioxins were detected in all samples except drinking water. The total concentration of OC in soils was Nd â 42.73 mg/kg, grasses (3.30 â 27.66 mg/kg), well water (0.82 â 1.00 mg/kg), feed mill (3.90 mg/kg), sera (Nd â 13.08 mg/kg) and meats (Nd â 100.72 mg/kg). Futhermore, the TEQ residues of TCDDs/TCDFs in beef were 4496.66 - 20642.40 pg/g from Yogyakarta, and 717.13pg/g (beef) and 0.037 pg/g (brain tissues) from Solo (Central Java). The concentration of TCDD/TCDFs residues in beef was above the maximum residue limit (MRL) at 2 pg/g. Animal feeds is regarded as the main source of dioxins contamination in meats. Macroscopic changes were general anaemia, cachexia, fibrotic liver, athropic heart, ruminal impaction, constipated intestinal, haemorrhagic kidney, and ptechiae in the brain. Microscopically were depleted spleen vacuolation of interseptum, haemorrhages and accumulation of hemosiderin. Heart shows degeneration, fragmentation and pale cardiac muscle and swollen nuclei. Liver was pale, degeneration of epithelial cells and congestion. Lungs were pneumonia, oedema pulmonum and mild haemorrhage. Intestines showed haemorrhage and infiltration of mononuclear cells, neutrophyls and eosinophyls. Brain was haemorrhage, perivascular cuffs and intranuclear inclusion bodies. The animal was suffering from haemorrhagic enteritis, encephalitis, and hepatic degeneration. Key Words: TCDDs, TCDFs, POPs, animal products, matrices, GC MS/MS